Legal Analysis of Sales Transactions with PayLater Payments - Rakka Dafa Maulana Oktavian; Mutimatun Ni'ami (IHSA Institute, 2026)
This study analyzes PayLater transactions from the perspective of Islamic law and Indonesian regulations to assess their compliance with Sharia principles. Using a qualitative descriptive-analytical approach, the research examines the operational structure of PayLater in relation to Islamic sales (ba’i) and financial transactions (muamalah), focusing on the prohibition of riba, gharar, and zulm. Primary sources include the Qur’an, Hadith, and fatwas from the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), while secondary sources consist of national regulations such as OJK Regulation No. 77/POJK.01/2016 and the Consumer Protection Law. The analysis finds that the current PayLater system contains elements inconsistent with Sharia principles, as its structure resembles a loan (qardh) with fixed interest, involves unclear contracts, lacks transparency, and imposes exploitative late fees. From a regulatory perspective, while PayLater is legally recognized, gaps remain in consumer protection, contractual fairness, and data privacy. Recommendations include adopting Sharia-compliant contracts such as murabahah, ijarah, or musyarakah, enhancing transparency, strengthening regulatory oversight, promoting financial literacy, and encouraging Sharia-certified digital financial products. Future research could empirically compare conventional and Sharia-based PayLater models to provide actionable insights